PP.32.23: A NEW ALGORITHM FOR THE DIAGNOSIS OF HYPERTENSION IN CANADA. (June 2015) - Gelfer, M.; Cloutier, L.; Daskalopoulou, S.; Padwal, R.; Lamarre-Cliche, M.; Bolli, P.; Mclean, D.; Milot, A.; Tobe, S.; Tremblay, G.; Mckay, D.; Townsend, R.; et al.
Abstract : Objective: Accurate blood pressure (BP) measurement is critical to properly identify and manage individuals with hypertension. For 2015 the Canadian Hypertension Education Program (CHEP) subcommittee on BP measurement and diagnosis conducted an in-depth review of the literature to determine the best current evidence-based practice for establishing a diagnosis of hypertension. Figure. No caption available. Design and method: Systematic literature searches from 2009 to 2014 were performed by a Cochrane Collaboration librarian in MEDLINE/PubMed. Members of the subcommittee reviewed the abstracts and selected the most relevant papers to be reviewed in depth. The results were presented to the CHEP Central Review Committee for a second review. Finally the recommendations, along with the supporting evidence, were presented to the full membership of the CHEP Recommendations Task Force for debate and voting. Results: Our literature review identified two major deficiencies in the current Canadian diagnostic process. 1. The auscultatory measurements performed in routine clinical settings have serious limitations in accuracy that have not been overcome despite great efforts to educate healthcare professionals over several years. Alternatives to auscultatory measurements should be used. 2. Patients with white coat hypertension must be identified earlier in the process and in a systematic manner rather than on an ad-hoc or voluntary basis so they are not unnecessarily treated with anti-hypertensive medications. Based on these critically important considerations, a revised algorithm for the diagnosis of hypertension was introduced. (Figure 1) Conclusions: The main take-home messages for the revised algorithm are: 1. For office BP measurement (OBPM) we strongly encourage the use of validated electronic digital oscillometric devices in place of auscultatory BP measurement. 2. When OBPM is elevated, out-of-office BP measurements should be performed to confirm the diagnosis of hypertension and rule out white coat hypertension. This should be done prior to the second visit. 3. For out-of-office measurement Ambulatory BP Measurement (ABPM) is the preferred method. If ABPM is not available or not tolerated by the patient, a diagnostic home BP measurement series (HBPM) should be performed. 4. If the out-of-office measurement is normal the patient should be diagnosed with white coat hypertension and pharmacologic treatment is not indicated.